Farbstoffe für die Energieumwandlung - Jürgen Rochlitz (CHIMIA)
The conversions of the energy of light into the electrical energy of photocurrents and photovoltages by organic dyestuffs has been reviewed. The primary and secondary processes of these conversions are very similar to those of the sensitization of photographic layers. Therefore some recent results with regard to the photographic sensitization are rounding the view of the practical application of charge carriers resulting from excited dye-molecules. Whereas during the process of photographic sensitization dyestuffs are used for more than hundred years, the replacement of Selenium in electrophotographic layers by similar and more efficient organic dyestuffs only succeeded in recent years. On the other hand till last year no dyestuffsystem was known, which was able to convert lightenergy into photovoltages at least nearly as efficient as inorganic semiconductors. However recently two dyestuffs have been found, which allow to assume converting-efficiencies for special dyestuffs in the same order of magnitude as those of inorganic semiconductors. Reaching the efficiency of selenium by dyestuffs was possible by a new process of sensitizing semiconductors. Instead of solved or dispersed dyestuffs a layer of the dye, only a few tenth of a micron thick, evaporated within high vacuum onto the grounding metal, sensitizes a transparent layer of an organic semiconductor, which only has a charge transporting function. Such dyestuff-double-layers with charge injecting dyes possess far better efficiencies than common organic photoconducting layers. Those dyestuffs are characterized by coloristic fastness and by slightly polarizable atoms. This last structural feature seems to be favorable for dyestuffs suitable in photovolta-cells, too. The dyestuff-double-layers are suitable for the investigation of charge-injection and -transport; this knowledge can lead to the conception of efficient photovolta-cells using dyestuffs, which could be less expensive than those using silicon for example.